(3eNJUQ GdeMUhds - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s; (3CHj YHO Gddg aNQ GdOjf eMeO Hf YeQ Hf GdMSjfj GdQGRj, GHf GdNWjH,J (B606 (3g` s ((3GdeOQSI GdeLGgOjI (B_ (3MeU s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeGFg bGd GdEeGe eMeO Hf YeQ GdQGRi gPG eNJUQ ai CUhd Gdabg EfJNHJg ef cJGH GdeMUhd hQJHJg Ydi ebOeI haUhd CeG GdebOeI aai JaSjQ CUhd Gdabg s
(3BNQgG (B:s
(3adh NQLJ Yf GdTQYjI cGf Pdc deYGQV hGdCUd YOe GdJYGQV hGddg GYde HGdUhGH Je GdcJGH HMeO Gddg hefg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hbO WGdYI GdfGSN ai SfI (B631(3g` HeOQSI GdeLGgOjI HMeU GdeMQhSI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3CUhd Gdabgs